Conservation discourses related to natural resource use : local communities and Kruger National Park conservation officers Mpumalanga Province, South Africa - Curtayne, Carmen (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.